Growth Respond of Three Tree Species on Tailing of Quartz Sand, Mined in East Belitung Regency RESPON PERTUMBUHAN TIGA JENIS TANAMAN PADA MEDIA TAILING BEKAS PENAMBANGAN PASIR KUARSA DI KABUPATEN BELITUNG TIMUR - Iwan Hilwan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Quartz sand is the main component of soil in heath forest floor which is very fragile in respond to any disturbance. The damaged heath forest after quartz sand has been mined, was very difficult to restore. Therefore, study on biophysical characteristics of primary and secondary heath forest are very important for improving forest rehabilitation efforts. After that, identification of tree species which is most suitable for the site in the rehabilitation program is very urgent. The research results showed that white jabon (Anthocephalus cadamba (Roxb.) Miq.) exhibited the greatest increase in height , diameter and dry weight (biomass). Therefore, white jabon is the best choice for rehabilitation on tailing of former quartz mined area. Planting media which are composed of tailing and organic matter (compost) is the best media for tree growth in rehabilitation program. The research results can serve as one of the guidances for stakeholders to manage heath forest in East Belitung Regency and as reference for rehabilitation activities.Key words: quartz sand, rehabilitation, tailing, white jabon